2018
DOI: 10.1155/2018/8475384
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Study on Diffusion Behavior of Chloride Ion in Cracking Concrete and Reinforcement Corrosion

Abstract: A chloride ion is a key factor affecting durability of reinforced concrete (RC) structures. In order to investigate chloride migration in cracked concrete, considering the mesoscopic heterogeneity of concrete, concrete modeled here is treated as a four-phase composite consisting aggregate, mortar, crack, and interfacial transition zone (ITZ). In this paper, two-dimensional finite element models of cracked concrete with different crack widths and crack quantity are established and the control parameters are det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…They concluded that increasing the water-to-cement (w/c) ratio results in a higher penetration rate of Clions, not only from the exposed surface but also from the area surrounding the cracks as well as from the exposed surface itself. For the most part, the penetration depth of the fracture surface is equal to or slightly greater than the penetration depth of the exposed surface, especially at higher w/c values of 0.45 and 0.65, according to conventional wisdom [51]. According to Kobayashi et al [52], the chloride proofing of concrete with fine cracks can be improved with a reduced w/c ratio and desirable fiber content.…”
Section: Chloride Ion Diffusion In Cracked and Uncracked Concretementioning
confidence: 99%
“…They concluded that increasing the water-to-cement (w/c) ratio results in a higher penetration rate of Clions, not only from the exposed surface but also from the area surrounding the cracks as well as from the exposed surface itself. For the most part, the penetration depth of the fracture surface is equal to or slightly greater than the penetration depth of the exposed surface, especially at higher w/c values of 0.45 and 0.65, according to conventional wisdom [51]. According to Kobayashi et al [52], the chloride proofing of concrete with fine cracks can be improved with a reduced w/c ratio and desirable fiber content.…”
Section: Chloride Ion Diffusion In Cracked and Uncracked Concretementioning
confidence: 99%
“…Zhou et al [47] studied the influence of 2D crack density (ρ) on effective permeability and found that crack connectivity is closely related to crack width, proving that the volume crack density and effective porosity have a certain linear relationship. Wang et al [48] comprehensively studied the crack characteristics of concrete and their effect on chloride ion penetration under the unsteady-state migration test Fig. 3 2D crack network and its characterization parameters.…”
Section: -100mentioning
confidence: 99%
“…In order to determine whether the localization results of AE events are consistent with the locations of real cracks, the locations of cracks (namely, cracks map) after beam failure are also obtained. According to the previous studies done by our team [33,34], image recognition technology can be used for depicting the cracks map. Since this work is not the focus of this study, it is briefly described here.…”
Section: Localization Of Ae Eventsmentioning
confidence: 99%